Analisis Penerapan Sak Etap Dalam Penyajian Laporan Keuangan Pada Koperasi Simpan Pinjam Dan Pembiayaan Syariah Nur Insani - Najla Sayyidina Syah Aurellya; Nurma Andriani; Najla Rani Sania; Tira Wulandari; Setia Apriana (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
Financial statements are an important means of communicating financial information from accounting activities and assisting decision making. General Financial Accounting Standards are often considered too complex for entities without public accountability, so that SAK ETAP is present as a simpler solution. This study aims to analyze the application of SAK ETAP in presenting financial statements at the Nur Insani Sharia Savings and Loans and Financing Cooperative. The method used is descriptive qualitative with analysis of cooperative financial statement documents. The results of the study indicate that the cooperative has attempted to implement SAK ETAP, but several shortcomings were still found, such as incomplete notes on financial statements and inconsistencies in account classification. This study recommends improving staff understanding and completeness of reports according to standards to support transparency and accountability of cooperatives.